Visual-vestibular and postural analysis of motion sickness, panic, and acrophobia - Coelho, Carlos M. (2017)
Trigger motion sickness and can also have a role in some anxiety disorders. We explore a method to detect individual sensitivity to visual-vestibular unusual patterns, which can signal a vulnerability to develop motion sickness and possibly anxiety disorders such as a fear of heights and panic. 65 undergraduate students were recruited for the purposes of this study as voluntary participants (44 females); average age 21.65 years (SD=2.84) with normal or corrected to normal vision, without vestibular or postural deficiencies. Panic was assessed with the Albany Panic and Phobia Questionnaire, Motion Sickness with the Motion Sickness Susceptibility Questionnaire and Acrophobia was assessed by means of the Acrophobia Questionnaire. The Sharpened Romberg Test was used to test participant’s postural balance. The Rod and Frame Test (RFT) measures the participant’s ability to align a rod to the vertical within a titled frame providing a measure of error in the perception of verticality by degrees. This test was changed to measure the error offered when a participant’s head was tilted, and to trace the error caused by manipulating the vestibular system input. The main findings show only motion sickness to be correlated with significant errors while performing a visual-vestibular challenging situation, and fear of heights is the only anxiety disorder connected with postural stability, although all disorders (fear of heights, panic and motion sickness) are correlated between each other in the self- report questionnaires. All disorders are correlated to each other in the surveys, and might have some common visual-vestibular origin, in theory. The rod and frame test was exclusively correlated with motion sickness whereas the postural stability test only displayed sensibility to acrophobia. Panic disorder was correlated to neither the RFT nor the Romberg. Although this method was initially employed to increase sensibility in order to detect anxiety disorders, it ended up showing its value in the detection of motion sickness.